2011
DOI: 10.1038/modpathol.2011.122
|View full text |Cite
|
Sign up to set email alerts
|

CD10 immunohistochemistry stains enteric mucosa, but negative staining is unreliable in the setting of active enteritis

Abstract: Ileal pouch-anal anastomosis is the definitive therapy for ulcerative colitis that is refractory to medical treatment or that has developed neoplasia. Patients with this procedure are routinely followed using directed endoscopic biopsies to monitor for dysplasia in the rectal cuff, residual/recurrent ulcerative colitis, and nonspecific acute inflammation of the ileal pouch (pouchitis), which have different clinical management and outcomes. Thus, accurate localization of mucosal biopsies is crucial to a definit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…NEP may have a role in the growth and differentiation of intestinal epithelial cells, and it has been used in support of diagnoses of microvilli inclusion disease using light microscopy[ 37 , 39 - 41 ]. In a study of ulcerative colitis patients, a regular staining pattern was detected in healthy ileal mucosa, but no staining was observed in inflamed mucosa[ 42 ], and changes in NEP expression were reported in a patient with intestinal metaplasia accompanied by gastric adenocarcinoma[ 43 ]. Moreover, we observed a more prominent diffuse CD10 staining pattern in the duodenal mucosa of patients without duodenitis than in those with duodenitis.…”
Section: Discussionmentioning
confidence: 99%
“…NEP may have a role in the growth and differentiation of intestinal epithelial cells, and it has been used in support of diagnoses of microvilli inclusion disease using light microscopy[ 37 , 39 - 41 ]. In a study of ulcerative colitis patients, a regular staining pattern was detected in healthy ileal mucosa, but no staining was observed in inflamed mucosa[ 42 ], and changes in NEP expression were reported in a patient with intestinal metaplasia accompanied by gastric adenocarcinoma[ 43 ]. Moreover, we observed a more prominent diffuse CD10 staining pattern in the duodenal mucosa of patients without duodenitis than in those with duodenitis.…”
Section: Discussionmentioning
confidence: 99%
“…Although NEP may act as an important anti-inflammatory molecule, its role in inflammatory bowel diseases such as in UC is not well explored. Loss of NEP immunoreactivity in a limited number of patients (n = 18) with this disease was demonstrated in a recent study by Lloyd and Owens [ 3 ].…”
Section: Introductionmentioning
confidence: 88%
“…All patients were informed of the study protocol verbally and in writing regarding the aim of the study, possible outcomes and adverse events that may occur during, and after, the procedure, with a signed informed consent. Sample size was calculated based on a study conducted by Lloyd and Owens [ 3 ], where NEP expression was lost by 20–80% in patients with UC. Sample size was calculated as twenty three patients per group, with an expected 50% loss of NEP expression in patients with UC (90% power and %95 confidence levels).…”
Section: Methodsmentioning
confidence: 99%
“…It is expressed in bone marrow lymphoid stem cells, pro-B lymphoblasts, and mature neutrophils and it is used for classification of leukaemias and malignant lymphomas (Lu et al 2016). It is also seen in the endometrial stroma and, with regards to the epithelium, it is found to be expressed in the lumina of renal tubules, hepatic sinusoids and the microvilli of the small intestine (Lloyd & Owens 2011;Iwase et al 2014;Katano et al 2017).…”
Section: Introductionmentioning
confidence: 99%